Comparison of the Success Rate of Mid and Distal Ureteric Calculi after Extracorporeal Shockwave Lithotripsy (ESWL) and Ureteroscopic Lithotripsy (URSL) in Nongkhai Hospital - นาคมนต์, ธงชัย (Journal of Health Science of Thailand, 2023)
There are several methods of treating ureteric calculi, including medication to relieve symptoms together with follow-up, Medical expulsive therapy, Extracorporeal shockwave (ESWL), ureteroscopic lithotripsy (URSL) and open ureterolithotomy. However, the choice of treatment depends on many factors. This study therefore aims to compare the success rate of middle and distal ureteric calculi after treatment with extracorporeal shockwave lithotripsy (ESWL) and ureteroscopic lithotripsy (URSL). It is a retrospective descriptive analysis in patients with mid and distal ureteric calculi in NongKhai Hospital for a period of 5 years from 2015-2020, totaling 196 cases, of which 139 were treated with URSL and 57 were treated with ESWL. The success rate was calculated from the rate of total stone removal after 4-6 weeks of treatment by comparing the treatment results of the two methods as follows: demographic data, stone characteristic data, the first session stone free rate, re-treatment rate, the second session stone free rate, auxiliary treatment and complication were collected. Data were analyzed using independent sample t-test, Chi-square test or Fisher’s exact test (95% CI, p<0.05). From this study, demographic data (such as age, sex, comorbidities, body mass index, and renal function) and stone characteristic data (such as the size of the stones, the number of stones) were not significantly different between both groups. The stone-free rate after the first URSL was 91.37% and 41.37% after the first ESWL treatment (p<0.001). ESWL group were significantly higher re-treatment rate than URSL group (URSL 1.44% & ESWL 35.05%, p<0.05). There was no significant difference between URSL group and ESWL group in the second session stone free rate (URSL 91.37% & ESWL 82.46%) and complications (URSL 1.43% & ESWL 0%). ESWL group was significantly shorter mean of hospital stay 0.30 day compared to 2.81 days in URSL group. In subgroup analysis, stone size ≤10 mm had significantly higher stone free rate than stone > 10 mm in URSL group. (Odd ratio 4.060, 95% CI=1.167–14.128). In conclusion, URSL had a higher first success rate of the middle and distal ureteric calculi than ESWL; and ESWL had a higher re-treatment rate compared to URSL. However, the success rate in the second ESWL treatment was the same as URSL.